1990
DOI: 10.1200/jco.1990.8.9.1514
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal therapy for the management of nonpelvic, localized Ewing's sarcoma of bone: intergroup study IESS-II.

Abstract: Two hundred fourteen eligible patients with previously untreated, localized Ewing's sarcoma of bone were randomized on IESS-II to receive Adriamycin (ADR; doxorubicin; Adria Laboratories, Columbus, OH), cyclophosphamide, vincristine, and dactinomycin by either a high-dose intermittent method (treatment [trt] 1) or a moderate-dose continuous method (trt 2) similar to the four-drug arm of IESS-I. Patient characteristics (sex, primary site, type of surgery) were stratified at the time of registration; these and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
165
2
5

Year Published

1996
1996
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 359 publications
(181 citation statements)
references
References 9 publications
9
165
2
5
Order By: Relevance
“…Prognosis of ESFT located in the vertebral column proved worse than that of patients with ESFT located in other sites. These data are also confirmed by results reported by other authors [14] and more in general by several series where prognosis of axial lesions is much worse compared to that of tumors located in the limbs [3,4,9,12,14]. Because of neighboring critical structures local treatment in ESFT of the vertebrae is an issue and local failure rate is higher.…”
Section: Discussionsupporting
confidence: 80%
“…Prognosis of ESFT located in the vertebral column proved worse than that of patients with ESFT located in other sites. These data are also confirmed by results reported by other authors [14] and more in general by several series where prognosis of axial lesions is much worse compared to that of tumors located in the limbs [3,4,9,12,14]. Because of neighboring critical structures local treatment in ESFT of the vertebrae is an issue and local failure rate is higher.…”
Section: Discussionsupporting
confidence: 80%
“…5,19,[35][36][37][38][39] In one randomized controlled trial in ES, 5 only 12.6% of patients were over the age of 18, whereas combining trials in ES which reported no impact of gender on outcomes, only approximately 25% of patients included were in the AYA age group. 5,19,35 The rarity of ES and OS in particular may present challenges of a statistical kind to stratification of outcomes by both age AND gender. Second, there may be fundamental biases in study design regarding dose modification rules.…”
Section: Discussionmentioning
confidence: 99%
“…The regimens that were applied are listed in Table 1. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] High-dose chemotherapy (HDC) with hematopoietic stem cell rescue was received by 51 patients, including 48 patients who received autologous peripheral blood stem cell transfusion (PBSCT) and 3 patients who underwent autologous bone marrow transplantation.…”
Section: Treatmentmentioning
confidence: 99%